Implications of Village Fund Policy on Shifts in Social Values of the Tului Village Community - Karjo Nalu; Mansyur Djamal (International Journal of Education, Information Technology, and Others, 2022)
Village fund policies not only have a positive impact on the community in development but also have a negative impact on shifting social values ​​in society. Shift in social values reflected in individual behavior in society, the behavior in question is an attitude of mutual cooperation, solidarity, and tolerance slowly starting to shift to a transactional attitude. The transactional attitude is a trigger for conflicts of interest for figures in the village so that social values ​​are no longer the basis of the community. Therefore, this study aims to explore social values ​​that have experienced a shift as an integral part of the implications of village fund policies. The approach used in this research is a qualitative approach with the type of case study research. This research was conducted in Tului Village, Oba District, Tidore Islands City by using observation, interview and documentation data collection techniques. While the sources use primary and secondary sources. The findings in this study explain that before the implementation of village funds was still strong in the life